PSEN1/SLC20A2 double mutation causes early-onset Alzheimer’s disease and primary familial brain calcification co-morbidity - Hebestreit, Sophie; Schwahn, Janine; Sandikci, Vesile; Maros, Máté E.; Valkadinov, Ivan; Yılmaz, Rüstem; Eckrich, Lukas; Loghmani, Seyed Babak; Lesch, Hendrik; Conrad, Julian; Wenz, Holger; Ebert, Anne; et al. (Neurogenetics, 2023)
Primary familial brain calcification (PFBC; formerly Fahr’s disease) and early-onset Alzheimer’s disease (EOAD) may share partially overlapping pathogenic principles. Although the heterozygous loss-of-function mutation c.1523 + 1G > T in the PFBC-linked gene SLC20A2 was detected in a patient with asymmetric tremor, early-onset dementia, and brain calcifications, CSF β-amyloid parameters and FBB-PET suggested cortical β-amyloid pathology. Genetic re-analysis of exome sequences revealed the probably pathogenic missense mutation c.235G > A/p.A79T in PSEN1. The SLC20A2 mutation segregated with mild calcifications in two children younger than 30 years. We thus describe the stochastically extremely unlikely co-morbidity of genetic PFBC and genetic EOAD. The clinical syndromes pointed to additive rather than synergistic effects of the two mutations. MRI data revealed the formation of PFBC calcifications decades before the probable onset of the disease. Our report furthermore exemplifies the value of neuropsychology and amyloid PET for differential diagnosis.